2007
DOI: 10.1073/pnas.0701152104
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hematopoietic stem cells in the bone marrow according to regional hypoxia

Abstract: The interaction of stem cells with their bone marrow microenvironment is a critical process in maintaining normal hematopoiesis. We applied an approach to resolve the spatial organization that underlies these interactions by evaluating the distribution of hematopoietic cell subsets along an in vivo Hoechst 33342 (Ho) dye perfusion gradient. Cells isolated from different bone marrow regions according to Ho fluorescence intensity contained the highest concentration of hematopoietic stem cell (HSC) activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
634
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 778 publications
(668 citation statements)
references
References 48 publications
22
634
1
11
Order By: Relevance
“…Examples of relatively hypoxic normal tissues include pericentral vein cells in the liver 12 , portions of the retina (in the dark) 13 , spinous layer of the epidermis 14 , the thymus 6,15 , renal tubular epithelium 16 , myocardium (particularly during exercise) 17 and subregions of the bone marrow that are enriched for stem cells 18 . Hypoxia has diverse roles in the function of these normal tissues.…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 99%
See 3 more Smart Citations
“…Examples of relatively hypoxic normal tissues include pericentral vein cells in the liver 12 , portions of the retina (in the dark) 13 , spinous layer of the epidermis 14 , the thymus 6,15 , renal tubular epithelium 16 , myocardium (particularly during exercise) 17 and subregions of the bone marrow that are enriched for stem cells 18 . Hypoxia has diverse roles in the function of these normal tissues.…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 99%
“…In the bone marrow the role of hypoxia is reversed relative to what is observed in skin. Here, the most primitive stem cells are maintained in a hypoxic niche 18 . These cells are maintained in a quiescent state by hypoxia-regulated proteins, such as osteopontin (encoded by SPP1) 18,25 .…”
Section: Regulation Of Hif1 By Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…The partial pressure of O 2 in human bone marrow is lower than in peripheral blood and the architecture of medullary sinuses and arterial blood flow patterns generate an O 2 gradient. It has been proposed that HSCs and their proliferating progenitors are naturally distributed along this gradient, with the HSCs occupying the most hypoxic niches 54,55 . Furthermore, Danet et al demonstrated that bone marrow HSCs cultured at 1.5% O 2 promoted their ability to engraft and repopulate the haematopoietic organ of immunocompromised recipient mice 56 .…”
Section: O 2 Levels Regulate Hematopoietic and Embryonic Stem Cellsmentioning
confidence: 99%